Absorption Cross Section and Decay Rate of Dilatonic Black Strings - Gursel, Huriye; Sakalli, Izzet (Hindawi Ltd, 2018)
We studied in detail the propagation of a massive tachyonic scalar field in the background of a five-dimensional (5D) Einstein-Yang-Mills-Born-Infeld-dilaton black string: the massive Klein-Gordon equation was solved, exactly. Next we obtained complete analytical expressions for the greybody factor, absorption cross section, and decay rate for the tachyonic scalar field in the geometry under consideration. The behaviors of the obtained results are graphically represented for different values of the theory's free parameters. We also discuss why tachyons should be used instead of ordinary particles for the analytical derivation of the greybody factor of the dilatonic 5D black string.
Keywords: Greybody Factors; Neutrino Oscillations; Holes; Particles